Air Pollution alongside Bike-Paths in Bogotá-Colombia - Franco, Juan F.; Segura, Julián F.; Mura, Ivan (Frontiers in Environmental Science, 2016)
The study we present in this paper aims at characterizing the range of fine particulate matter (PM2.5) and black carbon (BC) concentrations to which bike-path users in Bogotá are exposed to. Using a bike equipped with a DustTrak and a micro-aethalometer we measured PM2.5 and BC concentration levels along bike-paths corridors, during weekdays and weekends. Experiments were conducted in fours streets, representing four typical configurations of bike-paths in the city. Traffic data for workdays was also available from local mobility authority. Results indicate that bike-paths users in Bogotá are exposed to air pollution levels far exceeding the threshold values established as potentially dangerous for human health. Average concentrations for PM2.5 ranged between 80 and 136 ug/m3 in workdays and between 30 and 72 ug/m3 in weekends. BC mean concentrations were between 16 and 38 μg/m3 during workdays and in the range 10–32 μg/m3 during weekends. A statistically significant difference exists in the levels of pollutants concentrations measured during workdays and weekends for all the considered bike paths. According to our results, both traffic volume and diffusions conditions, which are affected by many factors including street geometry, affect bike-path user's exposure levels. Taking into account the important role that bicycling is playing as an alternative transport mode in Latin American cities, we consider these results provide useful insights to increase the appreciation of the excessive bikers' exposure to air pollution in Bogotá. Moreover, these findings contribute with technical elements that should lead to the inclusion of air quality variable when designing and planning sustainable urban mobility infrastructures.